2007
DOI: 10.1057/palgrave.crr.1550037
|View full text |Cite
|
Sign up to set email alerts
|

Images, Satisfaction and Antecedents: Drivers of Student Loyalty? A Case Study of a Norwegian University College

Abstract: Even if images and allied constructs, especially identity and reputation, have received considerable attention in recent years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
273
3
55

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(347 citation statements)
references
References 62 publications
(77 reference statements)
16
273
3
55
Order By: Relevance
“…These results support prior findings within the higher education sector. For example, satisfaction has been found to positively influence loyalty, resulting in positive recommendation and continuation of the student-university relationship (Hennig-Thurau et al 2001;Shah 2009;Helgesen & Nesset 2007). Satisfaction was also found to be positively and directly related to trust and affective commitment.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These results support prior findings within the higher education sector. For example, satisfaction has been found to positively influence loyalty, resulting in positive recommendation and continuation of the student-university relationship (Hennig-Thurau et al 2001;Shah 2009;Helgesen & Nesset 2007). Satisfaction was also found to be positively and directly related to trust and affective commitment.…”
Section: Discussionmentioning
confidence: 91%
“…A number of important determinants of student loyalty have been identified in prior research. Helgesen and Nesset (2007) for example, found that service quality, and social interaction, campus climate and the providers reputation positively influenced students' satisfaction with the institution. Similarly, Hennig-Thurau et.…”
Section: The Nature Of Student Loyaltymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, another set of authors consider that students can be regarded as a resource for university institutions and in turn, must also be considered as users in different contexts such as: in the application of EFQM models, the study of total quality management, perceived social responsibility, marketing, measurement of satisfaction and identification of customers, among others (Downey et al, 1994;Melle, 2003;Pitman, 2000;Modell, 2005;Helgesen, 2006;Helgessen and Nesset, 2007a;2007b).…”
Section: Introductionmentioning
confidence: 99%